FACTORS DETERMINING SHARIA RESPONSIBLE INVESTMENT STRATEGIES - Ida Busneti; Novi Imelda; Rizqullah; Yusuf Faisal (CV. Radja Publika, 2023)
This study aims to find out and analyze the factors that determine the strategy of sharia responsible investment principles to become a reference for the public in investment activities as part of the effort to realize sharia maqashid, especially in maintaining assets. The research methodology being used is the Analytic Network Process (ANP) by involving various experts and or practitioners in the field of investment and sharia economics. Numbers of journals are also used as references to determine problem variables, solutions and strategies. The results of the analysis extracted from the responses of the experts were concluded that (1) the existence of regulations such as reward & punishment and regulatory supervision is a problem in the application of sharia responsible investment principles, as well as successively (2) public awareness and fund managers - in this case an understanding of the benefits of sharia-responsible investing (3) the resources of investment managers and (4) the Islamic investment climate itself. Solutions to the problem of implementing sharia responsible investment strategies successively (1) providing tax incentives for Islamic investment funds managed in accordance with the principles of responsible investment (2) integration of capital market issuers (3) literacy & socialization to the public and related parties to increase understanding of sharia responsible investment (4) increase commitment of issuers and the existence of ESG-proven investment instruments supported by special ESG rating agencies.